(untitled) (Experimental biology, 2016)
Long-term experience of introduction in Mangyshlak arid conditions has revealed prospects of Armeniaca vulgaris cultivation. Armeniaca vulgaris is unpretentious in comparison with other introduced fruit plants species. Armeniaca vulgaris is luciphile, heat and salt resistant, easily propagate by seeds of local reproduction. 2 sorts (“Krasnoschyokiy”, “Nikitskiy Krasnoschyokiy”) and 13 sorto-clones (“Abrikosoviy vinograd”, “Gigant koturbulaka”, “Issykskiy ustoichivy”, “Katyusha”, “Koturbulakskiy neznyy”, “Krasa Dzhungari”, “Krasavitsa Kok-Bastau”, “Krupnoplodnyy rebristyy”, “Melkiy Karmin”, “Mikushinskaya repka” “Rekord Belbulaka”, “Chimkentskiy ranniy”, “Chimkentskiy sladkiy” of Armeniaca vulgaris from Kazakhstan selection are studied. Morphological studies and introduced grades description allowed to reveal a big variety of vegetative and generative organs morphology. At the same time their most general morphological features was identified. They are: light- green colors and oblong – elliptic forms of medium and small leaves with spinate tip, wide-stump bed, medium indentation with downiness (on the periphery of lamina), medium thickness and usually downiness leafstalk. In addition, knop sizes of Kazakhstan grades Armeniaca vulgaris big ranged. Small flowers with white and pink coloring of petals are dominated. A big variety of fruits sizes and forms was identified. Significant downiness is typically for most of apricot grades.